NEONATAL ACUTE MYELOID LEUKAEMIA - Luh Putu Rihayani Budi; Ketut Ariawati; Sianny Herawati (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2013)
Acute myeloid leukaemia (AML) is a. malignant, clonally disease that involves proliferation of blasts in bone marrow, blood, or other tissue. The blasts most often show myeloid or monocytic differentiation. The incidence of AML increases with age, but when neonatal leukaemia does occur, it is paradoxically AML rather than ALL. All the signs and symptoms that present on patient with AML are caused by the infiltration of the bone marrow with leukaemic cells and resulting failure of normal haematopoiesis. Without the normal haematopoietic elements, the patient is at risk for developing life-threatening complications of anaemia, infection due to functional neutropenia, and haemorrhage due to thrombocytopenia. Organomegaly is seen in approximately half of patient with AML due to hepatic and sphlanic infiltration with leukaemic blasts. Prognosis of neonatal leukaemia is poor with the 6-month survival rate is only one third despite aggressive chemotherapy. It has higher mortality rate than any other congenital cancer. The researchers reported two of AML diagnosed cases in neonatal period. The first case, a one-day-old male was referred with respiratory distress and suspect Down syndrome with spontaneous petechiae. The second case, a 17-day-old female presented with bloody diarrhoea and history of hypothyroid. Dysmorphic face and hepatosplenomegalia were found in both of the physical examination. Their complete blood count revealed leukocytosis and thrombocytopenia. Peripheral blood smear revealed myeloblast 30% on the first case and 23% on the second case. Both immunophenotyping revealed the population of blast expressing myeloid lineage (CD33 and CD34).